The Association of Autologous Mesenchymal Stem Cell Implantation to Clinical Outcomes in Knee Osteoarthritis - Achmad Munif; Christa Gisella Pirsouw (International Medical Journal Corp. Ltd, 2025)
Introduction: Knee osteoarthritis (OA) is a leading cause of pain and disability globally, driving the search for regenerative therapies. Autologous mesenchymal stem cell (MSC) implantation has emerged as a promising intervention aimed at pain relief, functional improvement, and potential cartilage repair. Methods: This systematic review synthesized evidence from 35 clinical studies (randomized controlled trials, cohort studies, and meta-analyses) investigating intra-articular autologous MSC therapy for knee OA. Studies were screened based on stringent criteria, including adult patients (≥18 years) with radiographically confirmed knee OA, autologous MSC source, intra-articular delivery, minimum 3-month follow-up, and reported clinical outcomes. Data were extracted on MSC characteristics, study design, patient demographics, clinical and structural outcomes, safety, and durability. Results: The analysis demonstrated that autologous MSC therapy yields statistically significant improvements in pain (e.g., VAS, WOMAC) and function (e.g., WOMAC, KOOS) compared to controls such as hyaluronic acid, saline, or placebo, with benefits often sustained for 12–24 months and up to 5 years in some studies (Lee et al., 2019; Lamo-Espinosa et al., 2018; Zhang et al., 2022). However, a substantial proportion of the observed improvement (approximately 50–66%) may be attributable to contextual (placebo) effects (Yin et al., 2025). Structural outcomes on MRI were heterogeneous, with significant cartilage regeneration reported primarily in early-stage OA (Kellgren-Lawrence grades I–II) (Tangkanjanavelukul et al., 2025; Ren et al., 2023), but not consistently in advanced disease. The dose-response relationship was inconsistent, and adipose-derived MSCs showed potentially superior efficacy to bone marrow-derived cells in some analyses (Zhang et al., 2022). The safety profile was favorable, with mostly transient local reactions and no serious treatment-related adverse events reported (Wiggers et al., 2021; Shoukrie et al., 2022). Discussion: The clinical benefits of MSC therapy appear most pronounced in patients with early to moderate OA, where regenerative potential remains. The dissociation between symptomatic improvement and structural changes highlights the role of MSCs' paracrine anti-inflammatory and immunomodulatory effects. Variability in outcomes can be explained by differences in OA severity, MSC source, processing methods, study design, and the significant influence of contextual effects. Conclusion: Autologous MSC injection is a safe and effective treatment for symptomatic knee OA, particularly in early to moderate stages. It provides meaningful, though modest, incremental benefit beyond placebo. Future research should prioritize standardized protocols, patient stratification by disease severity, and longer-term imaging studies to clarify disease-modifying potential.